Alphabetical index to the fifth edition (2012) of the Harmonized Commodity Description and Coding System and its explanatory notes (The Organization BrusselsBE, 2012)
Consists of an alphabetical listing of the articles and products mentioned in the Harmonized Commodity Description and Coding System (Harmonized System) and its explanatory notes.
Contents: v.1: A to L. - v.2: M to Z. On permanent loan to Single Market and Economy Sub-Programme (Mr. Breedy, Mr. Black, Mr. Watson).